The Problems of Ngaji online: The Book Ta’lim Muta’allim Perspectives - Muhammad Sulhan (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
In this article, the Problems of Online Recitation of the Book of Ta'lim Muta'allim, the focus of the study that the author carried out was on the chapter on the requirements for selecting knowledge, teachers and friends, seriousness and commitment in studying science, initial levels and learning methods, and time to study. knowledge. Online recitation is an Islamic learning practice that tries to adapt to advances in technology and information. However, in practice this activity has problematic sides in the values ??of etiquette in studying science and ineffectiveness in the process, content and learning methods and the absence of a formal institution that shelters it. This article is oriented towards analyzing the phenomena of the online Quran which is synchronized with the basic values ??or adab in studying science in the book of Ta'lim Muta'allim. The basic question in this article is what is the concept of online Quran? and how the online Quran is reviewed in the Ta'lim Muta'allim book. The approach that the author uses in this article refers to the basic rules in obtaining the benefits and blessings of knowledge, Shaykh Zarnuji. With the focus of the problem, namely, the widespread use of Islamic sites that are used to study religious knowledge in the midst of the community as a guide and understanding of religion. The method of presenting data is descriptive qualitative, data acquisition is through literature review. The findings of the online study of the Quran are the main alternative for individuals who do not have the opportunity and time to study religion directly and in formal institutions. And there are biases and gaps in the selection of knowledge, teachers, and friends, seriousness and commitment to learning, initial levels and learning methods as well as the time to study knowledge carried out in online Quran practices which have an impact on the lack of benefits and blessings of knowledge.